1983
DOI: 10.1038/306784a0
|View full text |Cite
|
Sign up to set email alerts
|

Patch- and voltage-clamp analysis of cyclic AMP-stimulated inward current underlying neurone bursting

Abstract: The second messenger cyclic AMP has been variously reported to affect the electrical activity of different neurones by decreasing outward potassium current, increasing outward current and increasing inward current. The recently developed patch clamp method of recording single ionic channels allows direct measurement of the action of cyclic AMP on membrane conductances. Using the patch clamp, the closure of potassium channels by cyclic AMP has previously been documented on the single channel level. We report he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
42
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 21 publications
9
42
0
Order By: Relevance
“…Analogous to this logic, it is interesting to speculate if 5-HT sulfate, but not 5-HT, regulates ApC/EBP diurnal expression in the eye (Hattar et al 2002). 5-HT neuromodulation in gastropod mollusks is mediated, in part, through the activation of slow, depolarizing ion currents readily observable in voltage clamp recordings of Aplysia and Pleurobranchaea MCC, buccal, and pedal G neurons (Green and Gillette 1983). Investigation of the electrogenic effects of 5-HT sulfate has so far not shown any of the excitatory effects exhibited by native 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to this logic, it is interesting to speculate if 5-HT sulfate, but not 5-HT, regulates ApC/EBP diurnal expression in the eye (Hattar et al 2002). 5-HT neuromodulation in gastropod mollusks is mediated, in part, through the activation of slow, depolarizing ion currents readily observable in voltage clamp recordings of Aplysia and Pleurobranchaea MCC, buccal, and pedal G neurons (Green and Gillette 1983). Investigation of the electrogenic effects of 5-HT sulfate has so far not shown any of the excitatory effects exhibited by native 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…An increased K+-current has been observed in response to bath and intracellularly applied cAMP or its analogs to molluscan neurons (TREISTMAN, 1981;EWALD and ECKERT, 1983). On the other hand, several investigators have reported that intracellular injections of cAMP cause either an increase in inward current (PELLMAR, 1981;ALDENHOFF et al, 1983;GREEN and GILLETTE, 1983;KONO-NENKO et al, 1983;CONNOR and HOCKBERGER, 1984), or a decrease in outward current (KLEIN and KANDEL, 1980;DETERRE et al, 1982;KACZMAREK and STRUMWASSER, 1984) across the molluscan neuronal membranes.…”
mentioning
confidence: 99%
“…The permeant, cyclic AMP analogue CPT-cyclic AMP has been shown to imitate the effects of intracellularly applied cyclic AMP in a number of preparations (see Gillette, 1983, andEwald &Eckert, 1983 for recent examples in molluscan neurones). This analogue, applied to the bathing medium at a 10/M concentration, caused an immediate and marked reduction in the K-dependent response to an ionophoretic application of carbachol (Fig.…”
Section: Effects Of Cholinergic Antagonists On the K Conductance And mentioning
confidence: 99%
“…14-2 elicits an inward current (see also Kononenko, Kostyuk & Scherbatko, 1983;Aldenhoff, Hofmeier, Lux & Swandulla, 1983b;Green & Gillette, 1983;Swandulla & Lux, 1984;Connor & Hockburger, 1984a). This inward current can be almost completely eliminated by increasing the Ca content of the sea water from 10 to 60 mM or by replacing the Na in the sea water by mannitol (see Fig.…”
Section: Effects Of Cholinergic Antagonists On the K Conductance And mentioning
confidence: 99%